Inactivity and overfeeding related changes in skeletal muscle composition and metabolism in captive felids - are they at risk of developing metabolic syndrome? - Feldmann, Daneil (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Obesity and physical inactivity are established key risk factors in the development of skeletal muscle insulin-resistance and type II diabetes in human and domestic animal populations. Wild animals are similarly exposed to these risk factors as a result of captivity. This study aimed at describing the skeletal muscle properties of captive lions (Panthera leo) who present with obesity and are physically inactive, with a group of free roaming wild lions. Skeletal muscle biopsies were collected from the Triceps brachii and analysed for fibre type composition, fibre size, and maximum oxidative (citrate synthase (CS), 3-hydroxyacyl CoA dehydrogenase (3HAD) and glycolytic (phosphofructokinase (PFK) and lactate dehydrogenase (LDH) enzyme capacities. The type IIA fibres were the predominant fibre type in both the wild (48%) and captive (44%) lions. No significant differences were evident in the overall fibre type composition between groups, although a trend towards less type I (28% vs 36%) and more type IIX (28% vs 16%) fibres in the captive group were observed. The captive lions displayed significantly larger cross-sectional areas (CSA) of the type I (5847μm² vs 3318 μm²) and IIA fibres (8344μm² vs 4360μm²) with no difference evident in the CSA of the IIX fibres. Relationships were observed between body mass and the CSAs of type I (r = 0.68, P = 0.0002) and IIA (r = 0.44; P = 0.03) fibres. Metabolically, the captive lions displayed higher flux through the glycolytic pathway as represented by their higher PFK activities (551 ± 287 vs. 338 ± 123 μmol/min/g protein, P < 0.05). In contrast, their CS activities (11 ± 3 vs. 14 ± 2 μmol/min/g protein) were lower than free roaming lions, suggesting lower oxidative capacity. No differences in LDH and 3HAD activities were observed between the two groups. Relationships were observed between 3HAD activity and MHC IIx fibre content (r = -0.43, P = 0.001), 3HAD activity and MHC I content (r = 0.55, P = 0.001). A positive correlation was observed between CS activity and MHC I content (r = 0.35, P = 0.009). In light of previous research, the data collected from this project follows that observed in exercise training models, where a sedentary lifestyle decreases oxidative capacity of muscle and increases type II fibre content. However, due to the low sample size in the free roaming wild lion group, interpretation of the data is difficult. Therefore, future research must strive to increase the sample number of the free roaming group.